Sex differentiation in grayling (Salmonidae) goes through an all-male stage and is delayed in genetic males who instead grow faster. Issue 1 (December 2017) - Maitre, Diane; Selmoni, Oliver; Uppal, Anshu; Marques da Cunha, Lucas; Wilkins, Laetitia; Roux, Julien; Mobley, Kenyon; Castro, Isabelle; Knörr, Susanne; Robinson-Rechavi, Marc; Wedekind, Claus
Abstract Fish populations can be threatened by distorted sex ratios that arise during sex differentiation. Here we describe sex differentiation in a wild grayling (Thymallus thymallus ) population that suffers from distorted sex ratios. We verified that sex determination is linked to the sex determining locus (sdY ) of salmonids. This allowed us to study sex-specific gene expression and gonadal development. Sex-specific gene expression could be observed during embryogenesis and was strong around hatching. About half of the fish showed immature testes around eleven weeks after fertilization. This phenotype was mostly replaced by the "testis-to-ovary" or "ovaries" phenotypes during development. The gonads of the remaining fish stayed undifferentiated until six months after fertilization. Genetic sexing revealed that fish with undifferentiated gonads were all males, who grew larger than the genetic females during the observational period. Only 12% of the genetic males showed testicular tissue six months after fertilization. We conclude that sex differentiation starts before hatching, goes through an all-male stage for both sexes (which represents a rare case of "undifferentiated" gonochoristic species that usually go through an all-female stage), and is delayed in males. During these juvenile stages males grow faster than females instead of developing their gonads.